Breast self-examination: knowledge, awareness, and practices among females of reproductive age group - Choudhary, Mamta; Mohanasundari, Sekkulandai K.; Ara, Meena (International Journal of Research in Medical Sciences, 2024)
Background: Breast cancer occurs in an observable organ, thus awareness regarding its symptoms can help in its early detection and treatment. Although breast self-examination (BSE) is an old technique, evidence reveals many of females are not aware regarding this, and those with knowledge about breast cancer examination either fail to practice it or do so incorrectly. Methods: It was a cross-sectional exploratory survey. 505 females attending outpatient department (OPD) at selected tertiary care hospital were recruited in the study using simple random sampling. Each participant was given a set of validated questionnaires to answer. The questionnaire was designed to obtain information regarding socio demographic data, knowledge, awareness, and practice regarding BSE. All data were coded, validated, and analyzed utilizing both descriptive and inferential statistics techniques. Results: The study revealed that the largest proportion (42.06%) of subjects fell within the age range of 20-30 years. Total mean score of knowledge and awareness regarding breast self-examination was 9.68±3.5. Maximum 58.42% of the subjects had average knowledge and awareness followed by 23.96% having good knowledge and awareness and least (17.62%) had poor knowledge and awareness regarding BSE. Almost half i.e., 50.49% (255) of participants reported to perform BSE and 49.51% of participants had never practiced BSE. Conclusions: The study revealed that while participants had average knowledge levels, they showed low involvement in routine BSE. This underscores the need for educational interventions to promote BSE practices, identify risk factors and warning signs, and encourage early-stage management of breast cancer, ultimately contributing to primary prevention in healthcare.